Kontribusi Mahasiswa KUKERTA dalam Meningkatkan Kebersihan Lingkungan di Desa Teluk Beringin - Wilda, Dwi Rahma; Putri, Endrisa Kurnia; Amalia, Fair Rizani; Hardiansyah, Hardiansyah; Yati, Ilmi; Maisura, Jumratul; Safitri, Nadira; Rume, Natasya Dewi Haya; Milda, Srinurma Okta (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Kukerta students at the University of Riau decided that the people in Teluk Beringin village needs to be socialized with waste management and also the provision of garbage disposal facilities there. With the concrete steps in the form of socializing and procuring of waste disposal facilities, it is intended that awareness and also the habit of disposing of waste in its place can grow in the community.